Learning Words That Stay: A Qualitative Exploration of Vocabulary Mastery in a Rural EFL Classroom - Nur Wulandari; Susi Astiantih; Hariadi Syam; Zakaria (South Sulawesi Education Development (SSED), 2026)
The mastery of vocabulary is obviously a key problem for English language learners, especially in rural areas where students have little access to English. The main objective of this study is to investigate the problems encountered by ninth graders in memorizing English vocabulary and, at the same time, look into methodologies utilized to enhance their mastery of vocabulary in a rural EFL classroom. One English teacher and 30 ninth-grade students of a rural junior high school in Indonesia were the participants of this descriptive qualitative research. Data were obtained through observations of classes, semi-structured interviews, and a document review. Results show that the students have battled hurdles to memorize new vocabulary because of a lack of frequent repetitions, inferior learning motivation, and inadequate chances for using English outside the classroom. Although various teaching methods, including vocabulary games, drilling, use of visual media, and rewriting-related activities, were presented in instruction, none of these strategies was used regularly or systematically. The vocabulary that students learned to memorize was retained at a low level. The research will help with incremental vocabulary mastery reinforcement via regular repetition, interactive learning, and vocabulary use in a meaningful context, mirroring the learner’s surrounding environment. These results underscore the need for vocabulary instruction customized to rural EFL class settings.